SPINA BIFIDA – ETIOLOGY, CLINICAL FEATURES AND MODERN MANAGEMENT - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Spina bifida is a complex congenital neural tube defect characterized by incomplete closure of the spinal column during early embryonic development. It is associated with significant neurological, orthopedic, and urological complications. This article reviews the etiology, classification, clinical manifestations, diagnostic methods, and modern management of spina bifida.